Enhanced Electrocatalytic Biodiesel Production with Chitosan Gel (Hydrogel and Xerogel). (2016) - Putra, Rudy Syah; Pratama, Kharis; Antono, Yudi; Idris, Muhammad; Rua, Jumardin; Ramadhani, Hikmat
Abstract: The production of biodiesel from used-cooking oil using the enhancement of electrolysis process with chitosan-gel (i.e. hydrogel and xerogel) as a base catalyst had been investigated. Previously, the optimized variables were evaluated by using soybean oil as a feedstock before using used-cooking oil on the biodiesel production. Biodiesel yield was influenced by chitosan-gel to oil mass ratio (0, 5, 10 and 15 wt. %), and electrolysis time (30, 60, 90 and 120 mnts). The methyl ester yields were determined by GC-MS on these operation variables. The results showed that the conversion of biodiesel increased with the increase of chitosan-gel to oil ratio thereby giving 98.0% yields respectively for 15 wt. % hydrogel, meanwhile in the similar mass ratio of chitosan-xerogel giving 94.5 wt. % yields, respectively. Contrary results showed that when electrolysis time increased, the conversions of biodiesel decrease thereby giving 99.4%, 98.5%, 97.1%, 98.2% yields respectively for 30, 60, 90 and 120 mnts. These optimized processes, e.g. 30 mnts and 15 wt. % catalyst, were then applied to convert biodiesel from used-cooking oil giving 90.3% for chitosan-hydrogel and 93.1% for chitosan- xerogel as a base catalyst, respectively.